Fibre Laser Cutting and Chemical Etching of AZ31 for Manufacturing Biodegradable Stents - Ali Gökhan Demir; Barbara Previtali; Carlo Alberto Biffi (Advances in Materials Science and Engineering)
The use of magnesium-alloy stents shows promise as a less intrusive solution for the treatment of cardiovascular pathologies as a result of the high biocompatibility of the material and its intrinsic dissolution in body fluids. However, in addition to requiring innovative solutions in material choice and design, these stents also require a greater understanding of the manufacturing process to achieve the desired quality with improved productivity. The present study demonstrates the manufacturing steps for the realisation of biodegradable stents in AZ31 magnesium alloy. These steps include laser microcutting with a Q-switched fibre laser for the generation of the stent mesh and subsequent chemical etching for the cleaning of kerf and surface finish. Specifically, for the laser microcutting step, inert and reactive gas cutting conditions were compared. The effect of chemical etching on the reduction in material thickness, as well as on spatter removal, was also evaluated. Prototype stents were produced, and the material composition and surface quality were characterised. The potentialities of combining nanosecond laser microcutting and chemical etching are shown and discussed.